Perancangan Keamanan Menggunakan Mikrotik Dengan Metode Layer 7 Protocol Dan Proxy Server - Qoyyimah, Diajeng Pipit Nurul; Amrulloh, Faishol (INFORMAL: Informatics Journal, 2024)
Security Design using Mikrotik with Layer 7 protocol and Proxy Server methods aims to enhance network security. In this design, Mikrotik will be configured as a firewall to filter and block unwanted internet traffic. Additionally, Mikrotik will also function as a router to manage internet traffic between the local network and the internet. In its implementation, the Layer 7 protocol method will be used to filter and restrict access to specific websites or applications, while the proxy server will be utilized to accelerate response times for repeated access requests and block access to undesirable websites or applications. The implementation of this design at SMK Darut Taqwa successfully blocked desired sites such as Facebook, TikTok, and Instagram, with the addition of filter rules to prevent any future site leakage. Furthermore, network administrators are able to control access to specific content.